A study of the validity and reliability of the Brazilian version of the Body Shape Questionnaire (BSQ) among adolescents Estudo de validade e confiabilidade da versão brasileira do Body Shape Questionnaire (BSQ) para adolescentes - Maria Aparecida Conti; Táki Athanássios Cordás; Maria do Rosário Dias de Oliveira Latorre (Instituto Materno Infantil de Pernambuco, 2009)
OBJECTIVES: to produce evidence of the validity and reliability of the Body Shape Questionnaire (BSQ) - a tool for measuring an individual's attitude towards his or her body image. METHODS: the study covered 386 young people of both sexes aged between 10 and 18 from a private school and used self-applied questionnaires and anthropometric evaluation. It evaluated the internal consistency, the discriminant validity for differences from the means, according to nutritional status (underweight, eutrophic, overweight and obese), the concurrent validity by way of Spearman's correlation coefficient between the scale and the Body Mass Index (BMI), the waist-hip circumference ratio (WHR) and the waist circumference (WC). Reliability was tested using Wilcoxon's Test, the intraclass correlation coefficient and the Bland-Altman figures. RESULTS: the BSQ displayed good internal consistency (±=0.96) and was capable of discriminating among the total population, boys and girls, according to nutritional status (p<0.001). It correlated with the BMI (r=0.41; p<0.001), WHR (r=-0.10; p=0.043) and WC (r=0.24; p<0.001) and its reliability was confirmed by intraclass correlation (r=0.91; p<0.001) for the total population. The questionnaire was easy to understand and could be completed quickly. CONCLUSIONS: the BSQ presented good results, thereby providing evidence of its validity and reliability. It is therefore recommended for evaluation of body image attitudes among adolescents. OBJETIVOS: verificar evidência de validade e confiabilidade do Body Shape Questionnaire (BSQ) - instrumento que mensura o aspecto atitudinal da imagem corporal. MÉTODOS: PArticiparam 386 jovens, de ambos os sexos, na faixa etária de 10-18 anos de uma escola particular de ensino, por meio de questionários auto-aplicáveis e avaliação antropométrica. Avaliou-se a consistência interna, a validade discriminante pelas diferenças das médias, segundo estado nutricional (baixo peso, eutrófico, sobrepeso e obesidade), a validade concorrente por meio do coeficiente de correlação de Spearman entre a escala e o Índice de Massa Corporal (IMC), a razão circunferência quadril (RCQ) e a circunferência da cintura (CC). Para confiabilidade, utilizou-se o teste de Wilcoxon, o coeficiente de correlação intraclasse e as Figuras de Bland-Altman. RESULTADOS: o BSQ apresentou boa consistência interna (±=0,96) e foi capaz de discriminar população total, meninos e meninas, segundo estado nutricional (p<0,001). Correlacionou-se com o IMC (r=0,41; p<0,001), RCQ (r=-0,10; p=0,043) e CC (r=0,24; p<0,001) e confirmou sua confiabilidade por meio da correlação intra-classe (r=0,91; p<0,001) para população total. Registrou-se boa compreensão e tempo de finalização. CONCLUSÕES: O BSQ apresentou bons resultados confirmando as evidências de validade e confiabilidade, sendo recomendado para avaliação do aspecto atitudinal da imagem corporal para adolescentes.